Undescribed meleagrin alkaloids from the endophytic fungus Penicillium commune. (December 2022) - Cao, Hai-Yan; Zhao, Jing-Yi; Yi, Cheng; Sun, Sen-Feng; Chen, Ke-liang; Qin, Zhi-min; Liu, Yun-Bao
Abstract: Six undescribed meleagrin analogues, isomeleagrin, meleagrin F, meleagrin G, methylmeleagrin G, isomethylmeleagrin G and meleagrin H, were isolated from the endophytic fungus Penicillium commune, which was obtained from the fresh leaves of a toxic medicinal plant, Tylophora ovata. The structures of these analogues were elucidated through extensive spectroscopic data analysis, and their absolute configurations were characterized by calculated electronic circular dichroism (ECD). Structurally, meleagrin F features an undescribed skeleton with an aniline moiety, which is linked to meleagrin through a C–C bond at C8–C26. Connecting N19–C3' through the C–N bond in meleagrin G, methylmeleagrin G, isomethylmeleagrin G and meleagrin H was rare for amino acid condensation. The cytotoxicity activity of these undescribed compounds was evaluated, and isomeleagrin exhibited a selective cytotoxicity activity against HGC27 cells with an IC50 value of 2.01 μM. Graphical abstract: Six undescribed meleagrins were isolated from the endophytic fungus Penicillium commune . Isomeleagrin exhibited a selective cytotoxicity activity against HGC27 cells with an IC50 value of 2.01 μM. Image 1 Highlights: Six undescribed meleagrins were isolated from fungus Penicillium commune. Meleagrin F features an undescribed skeleton bearing an aniline group. Connection of N19–C3' was rare for amino acid condensation. Isomeleagrin exhibited cytotoxicity activity with an IC50 value of 2.01 μM.